Kualitas Pelayanan Publik dalam Pembuatan Akta Kelahiran di Dinas Kependudukan dan Pencatatan Sipil Kota Gorontalo - Rahmatia Muhsin; Rosman Ilato; Irawaty Igirisa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Quality of Public Service in Issuing Birth Certificates at the Population and Civil Registration Office of Gorontalo City. Undergraduate Thesis. Bachelor's Degree Program in Public Administration, Universitas Negeri Gorontalo. The Principal Supervisor: Dr. H. Rosman Ilato, M.Pd. The Co-supervisor. Dr. Irawaty Igirisa, M.Si. This study aims to evaluate and analyze public service quality in issuing birth certificates at the Population and Civil Registration Office of Gorontalo City. The study was conducted by assessing the service through the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. Furthermore, it was conducted using a qualitative research method, utilizing observation, interview, and documentation data collection techniques. The findings reveal that the overall quality of public service, specifically within the Population and Civil Registration Office of Gorontalo City, assessed across five dimensions, are as follows: Tangibles are found to be lacking in facilities and infrastructure, such as seating, parking space, additional computers, and other informational media beneficial to the public. Reliability is noted as a concern, as staff are unable to provide accurate timelines for document processing. Responsiveness is adequate, with staff demonstrating a responsive attitude toward serving the public. Assurance remains suboptimal due to issues with service timeliness, and empathy is adequately demonstrated, with staff maintaining courteous interactions. Based on this analysis, it can be concluded that the quality of public service in the issuence of birth certificate at the Population and Civil Registration Office of Gorontalo City is not yet optimal. The researcher suggests that future improvements in facilities and infrastructure, along with enhanced staff performance, will lead to more efficient and reliable document issuance, reducing the need for repeated follow-ups by the public.